1998
DOI: 10.1021/jp9804190
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Charged Local Anesthetics into Model Membranes Formed by Cationic Surfactant:  Effect of Hydrophobicity of Local Anesthetic Molecules

Abstract: The partitioning of five hydrochloride salts of local anesthetics, dibucaine (DC‚HCl), tetracaine (TC‚HCl), bupivacaine (BC‚HCl), lidocaine (LC‚HCl), and procaine (PC‚HCl), into surface-adsorbed films and micelles formed by decylammonium chloride (DeAC) was studied by the surface tension of aqueous solutions of DeAC-local anesthetic mixtures. Thermodynamic quantities of the partitioning of the anesthetics, total surface density, and compositions of the anesthetics in the surface-adsorbed film and micelle were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The molecular mechanism of the pharmacological action for various drugs, such as anesthetics, is mediated by membranes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The interaction of anesthetic agents with excitable membranes is postulated to affect the specific trans-membrane proteins of the ionic channels by changing their membrane lipid micro-environment and thus, blocking the nerve signal propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of the pharmacological action for various drugs, such as anesthetics, is mediated by membranes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The interaction of anesthetic agents with excitable membranes is postulated to affect the specific trans-membrane proteins of the ionic channels by changing their membrane lipid micro-environment and thus, blocking the nerve signal propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to the present findings, it was found that the uncharged form of these substances was much more surface active than the corresponding hydrochloride salt. Furthermore, Matsuki et al studied the partitioning of hydrochloride salts of local anesthetics, among those lidocaine hydrochloride, to adsorbed layers formed by decylammonium chloride (67). Of particular interest to the present investigation, lidocaine HCl was found not to partition to the hydrophobic environment of the adsorbed layer, whereas for the adsorption of lidocaine HCl at the air-water interface significant adsorption at high concentration was observed (68).…”
Section: Effects Of Lidocaine and Prilocainementioning
confidence: 71%
“…These considerations are important when designing drug-release systems and also when considering the specific domain of a biological system where the drugs are selectively located. A case in point appeared in a recent study by surface tension of the partitioning of local anesthetics in model membranes (cationic surfactants): The results have indicated that the partitioning (in the water and micellar phases) depends on the hydrophobicity of the drug, and a good correlation was established between the partitioning into the hydrophobic environment and the anesthetic potency of the drugs.…”
Section: Discussionmentioning
confidence: 99%